2012
DOI: 10.1016/j.ijnt.2012.11.009
|View full text |Cite
|
Sign up to set email alerts
|

In decompressive craniectomy procedures it does not matter which way you do the duraplasty, or, does it? A study on an experimental model

Abstract: The pathophysiology of malignant intracranial hypertension is a deleterious cycle of increased intracranial pressure, decreased tissue perfusion, declining intracellular energy production, increasing cellular edema, and subsequent increasing intracranial pressure. Decompressive craniectomy offers an effective treatment for intracranial hypertension that is refractory to standard medical treatment. There is no standardized technique suggested for durotomy and expansile duraplasty till date. We conducted this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…A clay model-based study conducted in 2012 showed that with different forms of durotomy and expansive duraplasty, a 10 cm diameter craniectomy defect allows a volume expansion of approximately 120 cc when measured from the craniectomy defect, roughly corresponding to a true volume expansion of 20 cc. 6 An extensive literature search in March 2014 revealed a limited number of studies that had reported upon the craniectomy surface area and the resultant volume augmentation and/or the lateral bulge of the scalp flap. [12][13][14] However, in these studies, the flap displacement and volume expansion were measured from the level of the craniectomy margin using the Flint method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A clay model-based study conducted in 2012 showed that with different forms of durotomy and expansive duraplasty, a 10 cm diameter craniectomy defect allows a volume expansion of approximately 120 cc when measured from the craniectomy defect, roughly corresponding to a true volume expansion of 20 cc. 6 An extensive literature search in March 2014 revealed a limited number of studies that had reported upon the craniectomy surface area and the resultant volume augmentation and/or the lateral bulge of the scalp flap. [12][13][14] However, in these studies, the flap displacement and volume expansion were measured from the level of the craniectomy margin using the Flint method.…”
Section: Resultsmentioning
confidence: 99%
“…(i) A clay model-based study to find out effect of different durotomy and expansive duraplasty techniques on volume expansion. 6 (ii) A mathematical model-based study to decode the available data and determine an actual intracranial volume expansion achieved by the decompressive hemicraniectomy reported in the existing literature (►Fig. 2).…”
Section: Methodsmentioning
confidence: 99%